The hydrochorous Amazonian genus Glandonia (Malpighiaceae): new records, morphoanatomy updates and taxonomic contributions - Guesdon, Isabel Reis; Amorim, André Márcio; Meira, Renata Maria Strozi Alves (Phytotaxa, 2018)
Glandonia is a rare genus comprising three species confined to Amazonian rainforest. Glandonia macrocarpa has been documented in some localities of the lower Rio Negro, in the municipality of Manaus, Brazil. Glandonia prancei is represented by only a few herbarium specimens, which were collected along the Madeira and Purus rivers in the 1960s and 70s. A recent record of G. prancei was discovered while analyzing collections of G. macrocarpa, providing a new locality where we found and collected G. prancei. Glandonia williamsii, which had not been recorded in Brazil for the past three decades, was collected in the upper Rio Negro in this study. This work reexamines the taxonomy of the genus, based on fieldwork and herbarium specimens, and includes notes on morpho-anatomy, distribution and phenology. New morpho-anatomical characters are provided to better describe the species (e.g., outline of epidermal cell walls of the leaf, arrangement of petiolar vascular system, bracteole gland surface, and distribution of glands on the leaf blade and petals).